Diagnóstico da implementação de sistemas de gestão da qualidade em empresas construtoras e seus reflexos na gerência de materiais de construção - Dalmo Lucio Mendes Figueiredo (2006)
This paper presents an overview on the evolution of quality management systems, identifying the most significant tools that integrate the corresponding process. Moreover, it describes management systematic programs for conformity evaluation in Brazil, in view of the organizations that participate of the process. By analyzing the assimilation of quality management procedures on the civil construction sector, this work considered unfolding and difficulties that construction companies find as they are implanted. The factors that generate significant obstacles to the qualification process are identified by comparing the specific standards for the civil construction and the generic one, recognized internationally, and from research based on certification audit reports for the program "Qualification System for Civil Construction Companies". Furthermore, the impact on the management program for construction materials was also considered on this paper.